[Gullfoss From Above] - Streng, Evelyn Fiedler (1975)
Photograph of Gullfoss Falls from above. The waterfall falls down rock layers into the grey river water in the bottom right. Brown plains dotted in green grass surround the river at the top of the photograph to the left. A short mountain stretches across the top of the photograph in the background. Mist shoots up into the air on the right side of the photograph.